A modified Delphi consensus regarding the clinical utility of triplet therapy in patients with metastatic hormone-sensitive prostate cancer patients in the UK - Louisa Fleure; Amit Bahl; Suneil Jain; Vincent Khoo; Noel Clarke; Tania Kalsi; Hilary Glen; Junaid Mobeen (BMJ Open)
Objectives This study aimed to determine the clinical utility of the androgen deprivation therapy (ADT)+docetaxel (DOCE)+androgen receptor-targeted agent (ARTA) triplet therapy in patients with metastatic hormone-sensitive prostate cancer (mHSPC) in the UK.Design A modified Delphi method. A steering group of eight UK healthcare professionals experienced in prostate cancer care discussed treatment challenges, developing 39 consensus statements across four topics. Agreement with the statements was tested with a broader panel of professionals within this therapeutic area in the UK through an anonymous survey, using a four-point Likert scale. This was distributed by the steering group members and an independent third party. Following the survey, the steering group convened to discuss the results and formulate recommendations.Setting The steering group convened online for discussions. The survey was distributed via email by the clinicians and the independent third party.Participants Healthcare professionals involved in the provision of prostate cancer care, working in relevant professional roles (oncology, urology or geriatric consultant, oncology nurse specialist, and hospital pharmacist) within the UK. No patients or members of the public were involved within the study.Interventions None.Primary and secondary outcome measures Consensus was defined as high (≥75% agreement) and very high (≥90% agreement).Results Responses were received from 120 healthcare professionals, including oncologists (n=73), urologists (n=16), geriatricians (n=15), nurse specialists (n=11) and hospital pharmacists (n=5). Consensus was reached for 37 out of 39 (95%) statements, and 27/39 (69%) statements achieved very high agreement ≥90%. Consensus was not reached for 2/39 (5%) statements.Conclusions Based on the consensus observed, the steering group developed a set of recommendations for the clinical utility of ADT+DOCE+ARTA in treating patients with mHSPC in the UK. Following these recommendations enables clinicians to identify appropriate patients with mHSPC for triplet treatment, thereby improving patients’ outcomes.